2024
DOI: 10.2174/0929867331666230721154653
|View full text |Cite
|
Sign up to set email alerts
|

Anti-gout and Urate-lowering Potentials of Curcumin: A Review from Bench to Beside

Abstract: Background: Gouty arthritis is a complex form of inflammatory arthritis, triggered by the sedimentation of monosodium urate crystals in periarticular tissues, synovial joints, and other sites in the body. Curcumin is a natural polyphenol compound, isolated from the rhizome of the plant Curcuma longa, possessing countless physiological features, including antioxidant, anti-inflammatory, and anti-rheumatic qualities. Objective: This study aimed to discuss the beneficial impacts of curcumin and its mechanism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 134 publications
0
1
0
Order By: Relevance
“…137,140 As reported that GA was the most commonly associated with the acute stage of gout and was the most common presenting symptom of gout causing inflammatory symptoms. 141,142 Also, the chronic tophaceous gout stage is the most advanced stage of the disease and is characterized by the presence of tophi, which are deposits of urate crystals in the soft tissues with the less severe inflammation compared to the early stage. 139 It is implied that there must be some physiological and pathological activity that acts as a regulator of inflammation.…”
Section: Regulatory Role Of Nets In Ga Inflammationmentioning
confidence: 99%
“…137,140 As reported that GA was the most commonly associated with the acute stage of gout and was the most common presenting symptom of gout causing inflammatory symptoms. 141,142 Also, the chronic tophaceous gout stage is the most advanced stage of the disease and is characterized by the presence of tophi, which are deposits of urate crystals in the soft tissues with the less severe inflammation compared to the early stage. 139 It is implied that there must be some physiological and pathological activity that acts as a regulator of inflammation.…”
Section: Regulatory Role Of Nets In Ga Inflammationmentioning
confidence: 99%